Ensino de dança em litígio: uma problemática - Souza, João Batista Lima de (2017)
This thesis presents a discussion about the relations between the dance and physical education areas and aims to problematize the presence of dance in basic education. Even institutionalized for more than six decades in Brazilian higher education as an undergraduate course with specific qualifications [besides its own objectives, distinct egress profiles and delimited areas of activity] and despite the current legal regulation, the dance still needs to claim and reaffirm their spaces and their relevance in the schooling process. The accomplishment of the study evidenced the existence of different facets intertwined with its object, being that for its development a bibliographical investigation of documentary character and descriptive character was launched, in order to allow the establishment of an approach for the treatment of the different perspectives, evidenced after the examination of a set of official texts [laws, decrees and resolutions, for example] related to the subject. The thesis here is that in the drafting of these devices there are enunciations that open the way to interpretations that are not always convergent as to what would, in fact and in law, be the place of the graduate in dance in formal education - although this place is well delimited in the political-pedagogical projects of undergraduate dance courses. Some of these documents, and even their validity or legitimacy, are materialized at the core of many demands brought to the Federal Courts in all Brazilian regions, from which one can conjecture the existence of a kind of litigation that places, in the same arena of debates, professionals and representatives of both dance and physical education. The research is composed of a set of three chapters, along which the theme was approached. The work offers a systematization, state-of-the-art, consisting of theses, dissertations and annals of events that, in a variety of ways, are dedicated to understanding how the formation of dance teachers and physical education and the insertion of dance in the school environment. In addition, it would chronologically invent educational legislation and its implications both in higher education, in early childhood education and in primary and secondary education, seeking to emerge from the legal provisions listed the ethical, political and legal affiliations that may be giving rise to diverse conceptions of dance, body, art, science, teaching and learning. Such definitions influence the ways of appropriating human movement, allowing dance to be taken now as a form of expression and artistic modality, or as physical exercise and gymnastics modality, or as content to be taught in schools. Finally, the study points to the horizon of these relations, considering a constant need for [re] affirmation, in the area of dance, regarding its relevance in formal education, especially in a context where the performance of this historically, by physical education professionals.